Validation of the Work-Related Quality of Life Scale in Rehabilitation Health Workers: A Cross-Sectional Study - Ruotolo, Ilaria; Sellitto, Giovanni; Berardi, Anna; Panuccio, Francescaroberta; Simeon, Rachele; D'Agostino, Fabio; Galeoto, Giovanni (La Medicina del Lavoro, 2024)
Background: Work-related quality of life (WRQoL) is a multidimensional concept related to life satisfaction. Evaluating WRQoL is essential in healthcare settings since employee satisfaction affects patient service quality. Only a few studies have focused on the quality of life of rehabilitation health workers. We aimed to validate the Italian version of the WRQoL scale on a population of rehabilitation health professionals; the secondary objective was to investigate the work-related quality of life of professionals concerning the work settings in which they operate. Methods: Participants were recruited from January 2022 to December 2023 according to specific inclusion criteria. Questionnaires were administered through an online survey requiring also personal employment data, and together with the SF-12 questionnaire, a test-retest was performed on 30 therapists. Reliability was assessed with Cronbach's alpha, test-retest stability through intraclass correlation coefficient (ICC), and concurrent validity was calculated using Pearson's correlation. Results: We enrolled 284 individuals. Internal consistency analysis showed statistically significant results: Cronbach's alpha was > 0.70; construct validity analyses revealed statistically significant data for total scores and subscales, compared to SF-12 scores. Conclusion: The WRQoL scale is a valid and reliable tool to assess the quality of working life of rehabilitation professionals.